MANAJEMEN AKREDITASI PROGRAM STUDI PADA PERGURUAN TINGGI - YULIANINGSIH, YUYUN (Universitas Islam Negeri Raden Intan Lampung, 2015)
Accreditation is one form of assessment (evaluation) the quality and feasibility study program at the university conducted by an independent organization or agency outside the college that is BAN-PT. The program of study as the spearhead of college should really be administered in implementing its program of good quality. The fact shows that the existing courses within the college while more needs to be managed with maximum especially the problem of lecturers so that the ratio of lecturers and students is really ideal. Departing from this fact, it will be necessary to find the problems that cause these conditions occur. Therefore, the purpose of this paper to discuss the legal basis of accreditation, management quality of study programs, objectives and benefits of accreditation, the components of accreditation of courses that consist of: a standard of accreditation, procedure of accreditation, accreditation instruments courses, and codes of conduct, as well as the acceleration strategy accreditation.